PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK PSIKODRAMA TERHADAP EFIKASI DIRI SISWA KELAS VIII SMP NEGERI 29 SEMARANG - Laksono, Tri Bowo (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
Tri Bowo Laksono. 14110169. "The Effect of Group Counseling Services with Psychodrama Techniques on the Self-Efficacy of Class VIII Students of SMP Negeri 29 Semarang". Thesis. Guidance and Counseling Study Program. Faculty of Science Education. PGRI Semarang University. Dra. Tri Suyati, M. Pd. Ismah, S. Ag., M. Pd. December 2019. This study aims to determine the effect of group guidance services with psychodrama techniques on the self-efficacy of students at SMP Negeri 29 Semarang. The research method used is true experimental with pretest-posttest control group design. The population in this study were students of class VIII SMP N 29 PGRI Semarang in the 2018/2019 academic year totaling 219 students consisting of 7 classes, one class was used for try-outs, while the sample consisted of one class used as research samples. The total number of samples was 189 students. The sampling technique used was cluster random sampling technique. Student self-efficacy values ​​were obtained from pre-test and post-test scores. The analysis used to test validity is the product moment correlation and reliability using the alpha formula. T test analysis results that the posttest between the experimental group and the control group obtained the t-count = 10.3. To ensure whether the difference is significant, the results are consulted with a table. With db = (n1 + n2) -2 = (15 + 15) -2 = 28 and a significant level of 5%, a ttable = 2.021 is obtained. Because tcount = 10.3 ˃ ttable = 2.021 then tcount is greater than ttable meaning Ho is rejected and Ha is accepted, so it can be concluded that "There is an influence of group guidance services with psychodrama techniques on self-efficacy in class VIII SMP N 29 Semarang.", Suggestions what researchers can convey should be the supervising teacher at the school providing follow-up services with regard to developing self-efficacy.